Agro-Industrial Clusters as a Factor of Increasing Competitiveness of the Region - Doronina, Iuliia I.; Borobov, Vasilii N.; Ivanova, Elena A.; Gorynya, Ekaterina V.; Zhukov, Boris M. (International Journal of Economics and Financial Issues, 2016)
There are two main and urgent problems in modern development of regions’ economy concerning the transition of interregional divergence and the transition of difficult regions to a model of "catch-up" development and the determination of new more competitive forms of their spatial organization development. Best practices and theoretical studies of future development reorganizations in reference Russian regions allow to consider agro-industrial clusters as such a form. A cluster approach formed taking into account affirmative synergetic effects of a regional agglomeration, network effects, diffusion of innovations can be an accelerator of social and economic attitude development of difficult regions, prevent deprivation of rural territories. Development of general agreements of clustering is combined with development of a complex system of strategic planning of the cluster territory creation. A development plan of an agro- industrial cluster and a program of its realization are reasons for e implementation of complex state support of cluster initiatives and cluster potential attitude development. Thus, an imperative of economic space causes the need for modernization of program-oriented and goal oriented management of social and economic development of difficult regions, rural areas of the formation of a cluster strategy and network models of interaction in an agro-industrial complex. Keywords: Cluster, creation, agricultural industry, region, competitiveness, agriculture. JEL Classifications: A19, A10, J43